KEWENANGAN OTORITAS JASA KEUANGAN MENGENAI PERLINDUNGAN HUKUM BAGI INVESTOR TERHADAP TINDAKAN TIPPEE YANG MELAKUKAN INSIDER TRADING DALAM PERDAGANGAN SAHAM - Juliana, Made Dwi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
One type of a criminal in the capital market is the practice of  insider trading. Insider trading is an act that involves a group of insider in the capital market who deliberately exploit information that has not been released to investors with the advantages. In insider trading there are two actors such as party directly as an insider who works in the company or indirect as tippee party who obtain confidential information from an insider. Tippee is the party who receives confidential information from an insider either passively or actively against the law or not against the law for personal gain in the stock trading. This is very detrimental to the investors in the stock trading. Because of that if needs the protection for investors against the actions of the Tippee.  This study discusses two (2) problem first about the subject matter of the action form Tippee in insider trading to the stock at Indonesia and the second about OJK authority on legal protection for investors in case of insider trading by the Tippee in capital market activities. This research is a normative law. The Method approach is the approach of legislation, conceptual approach and comparative approach. Legal materials used are primary and secondary legal materials. Mechanical collection of legal materials is through the study of literature that further uses analysis techniques that description techniques and interpretation. The results shows that this form of action Tippee can be done actively and passively. Actively to perform an unlawful act such as stealing information. In is not trying to fight the law, but to obtain inside information and legal safeguards for investors to act with regard to insider trading Tippee do give legal certainty through legislation and legal certainty by the OJK through law enforcement
Keywords: Insider; Tippee; Investors; Insider Trading; Legal Protection